ANALYSIS OF SAMSAT SERVICES TO COMPULSORY OF MOTOR VEHICLES TAXPAYERS (Empirical Study In Karanganyar District) - Ratnasari, Christiana Putri; Sulisyani, Lilis (STIE AUB Surakarta)
This study aims to analyze the effect of Tax Access, Facilities, Complain Center and Website to Taxpayer Compliance In Karanganyar District. The population in this study are all Motor Vehicle Taxpayers registered in Karanganyar District. Sampling technique using random sampling technique with the number of samples of 100 respondents. Analytical techniques consist of Validity Test, Reliability Test, Multicolinearity Test, Autocorrelation Test, Heteroscedasticity Test, Normality Test, Multiple Linear Analysis, T test, F Test, and Coefficient of Determination. Hypothesis Test Result proves that Access Taxes, Facilities, Complaint Center, and Website have positive and significant impact to Taxpayer Compliance. F test results prove that Tax Access, Facilities, Complaint Center, and Website together have a significant effect on Taxpayer Compliance. The result of determination test (R2) proves that the overall influence given by independent variable to the dependent variable is 31.3% while the rest of 68,7% is influenced by variable or other model not included in this research.Keyword: Tax Access, Facilities, Complain Center and Website, Taxpayer Compliance